y = x2 is the parent function, but it can be in the form y = ax2 + bx + c
A quadratic involving x and y is usually in the form 'y = ax2 + bx + c'. This form is y in terms of x, so we must rearrange it. y = ax2 + bx + c y/a = x2 + bx/a + c/a y/a = x2 + bx/a + d + e, where c/a = d + e, e = (b/a)2 y/a - e = x2 + bx/a + d y/a -e = (x + b/a)2 √(y/a - e) = x + b/a √(y/a - e) - b/a = x
There are two degrees to a quadratic equation, as the x2 term is present. General form of a quadratic equation: Ax2+Bx+C
x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0
This is called an incomplete quadratic equation because there is no linear term. aX2 +( bX)+ c = 0 The middle term is not there, but this is quite solvable.
2x^2 + 8x + 3 = 0
x2+bx+ax+ab = x2+ax+bx+ab = x(x+a)+b(x+a) = (x+a)(x+b)
The general form of a quadratic expression is given as ax2+bx+c where "a" cannot equal zero and "b" is the coefficient of the variable "x" and also the sum of the factors of "c" when "a" is unity. Example: x2+5x+6 = (x+2)(x+3) when factored
In a word, yes. Any simplified form that has 3 terms is a trinomial, but is often in the form ax2 +bx +c where a,b,c are real numbers.
x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0
blank spaces are a (+) sign and (=)